Marketing at the confluence between entertainment and analytics : proceedings of the 2016 Academy of Marketing Science (AMS) World Marketing Congress /: proceedings of the 2016 Academy of Marketing Science (AMS) World Marketing Congress. ([2017]) - Unknown
No abstract available